2003
DOI: 10.1007/s00244-003-2201-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy

Abstract: Liver samples of 12 species of birds of different trophic levels, collected during the period 1998-2000 from coastal areas of the Campania region, Southern Italy, were analyzed for organochlorine pesticides (OCs), such as dichlorodiphenyltrichloroethane (DDT) and its metabolites, hexachlorobenzene (HCB), gamma-hexachlorocycloexane (gamma-HCH), aldrin, dieldrin, endrin, and the seven PCB "target" congeners, IUPAC Nos. 28, 52, 101, 118, 138, 153 and 180. p,p'-DDE was present in all the samples analyzed, at conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
19
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 37 publications
10
19
3
Order By: Relevance
“…in paddy fields has been reported 10 . Predominant accumulation of 4,4 -DDE in carnivorous birds was consistent with other studies which found it to be the most frequent OCP detected in wild bird tissues due to its high persistence and lipophilicity [26][27][28] . ΣHCH contamination was moderate (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…in paddy fields has been reported 10 . Predominant accumulation of 4,4 -DDE in carnivorous birds was consistent with other studies which found it to be the most frequent OCP detected in wild bird tissues due to its high persistence and lipophilicity [26][27][28] . ΣHCH contamination was moderate (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…2). Similar results were also reported in the liver of birds collected from the coastal area of Campanis, Italy 28 . Birds that feed exclusively on fish have been shown to be at higher contamination risk than birds those feeding at lower trophic levels due to their low monooxygenase activity, resulting in lower biotransformation of xenobiotics and subsequent biomagnification 1,33,34 .…”
Section: Discussionsupporting
confidence: 87%
“…In general, the contamination burden in both male and female house sparrows in the present study was low compared to studies of birds of prey (Naso et al, 2003). Nevertheless, negative relationships between POPs and estrogens were observed in female house sparrows.…”
Section: Discussioncontrasting
confidence: 69%
“…This predominance is most likely due to the lipophilic and persistent nature of hepta-, hexa-and penta PCBs to facilitate absorption and accumulation. In addition, it is well known that higher chlorinated PCBs exhibit higher bioaccumulation in avian tissue than lower chlorinated congeners (Naso et al, 2003) due to their molecular structure and chemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…They are situated high on the food chain, thus accumulating high levels of organohalogenated pollutants, and they are sensitive to environmental changes (Furness, 1993). The amount of organohalogenated pollutants accumulating within the tissues of birds is related to their diet and corresponding trophic position (Borgå et al, 2004;Naso et al, 2003), but also to differences in accumulation among habitats and ecosystems (marine versus terrestrial).…”
Section: Introductionmentioning
confidence: 99%